2022
DOI: 10.1111/bcp.15365
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of psychoactive substances in blood samples from non‐fatal and fatal opioid overdoses

Abstract: The primary aim was to compare concentrations of psychoactive substances in blood in non-fatal and fatal opioid overdoses. The secondary aim was to assess the concentration levels of naloxone in blood in non-fatal overdoses and the association between naloxone findings and concomitantly detected drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(81 reference statements)
0
3
0
1
Order By: Relevance
“…This may seem high in comparison with the literature; for example, Edvardsen et al. [38] found that the median number of drugs present in fatal opioid overdose cases was four, and five for non‐fatal opioid overdoses. This difference can be explained by differences in drug concentrations, suggesting that both the combination of high levels of these drugs, and the number of different drugs present are important factors to consider.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This may seem high in comparison with the literature; for example, Edvardsen et al. [38] found that the median number of drugs present in fatal opioid overdose cases was four, and five for non‐fatal opioid overdoses. This difference can be explained by differences in drug concentrations, suggesting that both the combination of high levels of these drugs, and the number of different drugs present are important factors to consider.…”
Section: Discussionmentioning
confidence: 72%
“…Edvardsen et al. [38] reported concentrations between 0.09 and 5.57 ng/mL, observing a linear relationship between the blood concentration of naloxone and the concomitant pooled opioid concentration. We did not observe the same trend, as the concentrations for four of the five most frequently detected opioids were not significantly different between groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Da samarbeidet ble inngått, ble det knyttet følgeforskning til tilbudet for å se på pasientkarakteristika og blodkonsentrasjoner av rusmidler hos pasientene (11). Vi fulgte derfor nøye med på hvor mange som benyttet seg av tilbudet.…”
Section: K O N T E K S T F O R S T U D I E Nunclassified